2012
DOI: 10.1007/s10067-012-2135-9
|View full text |Cite
|
Sign up to set email alerts
|

Transfer from paediatric rheumatology to the adult rheumatology setting: experiences and expectations of young adults with juvenile idiopathic arthritis

Abstract: Adolescents with juvenile idiopathic arthritis (JIA) are transferred from paediatrics to adult-oriented healthcare when they reach early adulthood. Research on the extent to which patients' expectations about the adult healthcare setting match their actual experience after transfer, may promote successful transfer from paediatrics to adult care. As part of the 'Don't Retard' project ( http://www.kuleuven.be/switch2/rheuma.html ), experiences and expectations of young adults regarding their transfer from paedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…The need for their transition to adult care has posed numerous challenges for pediatric health care providers. Several studies have investigated preferences, expectations, and concerns of adolescents with different chronic conditions and their parents or family . Our study reports the current state of transition to adult pulmonary specialty care of pediatric patients with chronic respiratory disease requiring the use of respiratory technology to maintain stability as perceived by physicians in ACGME‐accredited pediatric pulmonary fellowship programs.…”
Section: Discussionmentioning
confidence: 99%
“…The need for their transition to adult care has posed numerous challenges for pediatric health care providers. Several studies have investigated preferences, expectations, and concerns of adolescents with different chronic conditions and their parents or family . Our study reports the current state of transition to adult pulmonary specialty care of pediatric patients with chronic respiratory disease requiring the use of respiratory technology to maintain stability as perceived by physicians in ACGME‐accredited pediatric pulmonary fellowship programs.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this particular qualitative study corresponds to the modelling phase of the MRC framework (figure 1, green box). The methods and results of this first qualitative study are reported in two related articles 21 22. Therefore, we do not elaborate on this study in the present article.…”
Section: Methods and Designmentioning
confidence: 99%
“…Common barriers to transition include lack of preparation, difficulties ending existing relationships with pediatric clinicians, and negative attitudes toward adult services. [6][7][8] Research into transition has moved away from transition policy and position papers toward exploring stakeholder views in order to gain more in-depth understanding of transition experiences and variables that contribute to success or failure. 9 The majority of these studies have been with young people and parents or caregivers, 6,10 and studies exploring HCP views have been relatively few and mainly in other specialties.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…9 The majority of these studies have been with young people and parents or caregivers, 6,10 and studies exploring HCP views have been relatively few and mainly in other specialties. [6][7][8][9]11,12 One recent quantitative survey involving 236 hepatologists identified that formalized transition programs are uncommon in adult hepatology clinics, with poor adherence and limited patient knowledge seen as barriers to optimal care. 13 A further study identified that team climate, defined as "a team's shared perceptions of organizational policies, practices, and procedures," 14 and changes in team climate predicted the quality of transitional care to chronically ill adolescents.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation